Single Questions for the Screening of Anxiety and Depression in Hemodialysis. Issue 1 (January 2019) - Collister, David; Rodrigues, Jennifer C.; Mazzetti, Andrea; Salisbury, Kelsi; Morosin, Laura; Rabbat, Christian; Brimble, K. Scott; Walsh, Michael
Background: Depression and anxiety are common and underrecognized in end-stage renal disease (ESRD), are associated with poor outcomes and reduced health-related quality of life, and are potentially treatable. Simple, accurate screening tools are needed. Objective: We examined the operating characteristics of single questions for anxiety and depression from the Edmonton Symptom Assessment System (ESAS) in hemodialysis. Design: Cross-sectional study. Setting: Two outpatient hemodialysis units (1 tertiary, 1 community) in Hamilton, Canada. Patients: Adult prevalent hemodialysis patients. Measurements: ESAS and Hospital Anxiety and Depression Scale (HADS). Methods: Participants were asked the degree to which they experienced anxiety and depression using the ESAS. ESAS single questions for anxiety and depression were compared with the reference standard of the HADS using dialysis population specific cutoffs (HADS anxiety subscale ≥6 and HADS depression subscale ≥7). Logistic regression was used to create receiver operating characteristics (ROC) curves. Results: We recruited 50 participants with a mean age of 64 (SD = 12.4) years, of whom 52% were male and 96% were on ≥3× weekly hemodialysis. Using the reference standards, 28 (56%) had a diagnosis of anxiety and 27 (54%) had a diagnosis of depression. Areas under the ROC curves were 0.83 for anxiety and 0.81 for depression using ESAS scores of ≥2. Limitations: Sample size and the lack of a reference gold standard. Conclusions: The ESAS single questions for anxiety and depression have reasonable discrimination in a hemodialysis population. The use of more complex and time-consuming screening instruments could be reduced by adopting the ESAS questions for anxiety and depression in hemodialysis.